What happened to foreign outsourcing when firms went online? - Aoife Hanley; Ingrid Ott (Kiel Institute for the World Economy (IfW), 2012)
The possibility to outsource over the internet should revolutionize foreign outsourcing, especially for services (UNCTAD, 2004). Our model describes materials and services input allocation from domestic vs. foreign suppliers. Allocations change when firms outsource online due to access and competition effects. Using data for 99 firms who started outsourcing online in 2003 together with a control group (never outsourcing online) of over 682 Irish firms, we apply OLS and Propensity Score Matching with Difference-in-Differences to find that 42-48 percent of foreign services inputs growth arises from online outsourcing.
Keywords: L23; 330; International Outsourcing; Propensity Score Matching; Input Price Uncertainty; Input Demand; Outsourcing; International; Internet; Lieferanten-Kunden-Beziehung; Internationaler Dienstleistungsverkehr; Schätzung; Irland